ENHANCING JUNIOR HIGH SCHOOL STUDENTS’ SPEAKING SKILLS THROUGH TASK-BASED LANGUAGE TEACHING (TBLT) - Eryana Putri, Febriyanti; Kusrin; Nina Puspitaloka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students in English as a Foreign Language (EFL) classrooms often face difficulties in developing their speaking skills due to limited vocabulary, pronunciation problems, and low self-confidence, which hinder their ability to communicate effectively. To address this issue, this study aimed to analyze the implementation of Task-Based Language Teaching (TBLT) in improving students’ speaking skills and to explore their perceptions toward its use in the classroom. The research was conducted in a junior high school in Karawang, Indonesia, involving one English teacher and 40 eighth-grade students, with six purposively selected as interview participants. A qualitative case study design was employed, using classroom observations and semi-structured interviews as the main techniques of data collection. Thematic analysis was applied to interpret the data. The findings show that TBLT was implemented through three stages, namely pre-task, task cycle, and post-task, using recount texts as the learning material. During these stages, students actively participated in pair discussions, presented their work, and received feedback, which contributed to the improvement of their classroom engagement and confidence. Nevertheless, several challenges were identified, including vocabulary limitations, pronunciation difficulties, and variations in students’ levels of confidence. Overall, students perceived TBLT positively, emphasizing that collaborative learning and meaningful tasks encouraged them to be more active in communication. This study concludes that TBLT plays a significant role in enhancing students’ speaking skills and provides practical implications for EFL teachers in designing interactive and student-centered learning activities.